Pengembangan Media Diosia Berbasis QR Code melalui Pembelajaran Berbasis Masalah untuk Meningkatkan Self-efficacy Dan Pemecahan Masalah Siswa Kelas V SD - Andarista, Elsa; Alfi, Cindya; Amalia, Shofi Nur (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2025)
The purpose of this study was to determine the level of validity, the feasibility of the media diosia, and to find out the increase in self efficacy and problem solving through the 5th grade diosia media at SDN Ngadipuro 04. Background This research is due to the low self -confidence of students due to the lack of learning media. This research applies the Reseach and Development method using the Assure development model. The subject used at this stage was 5 SDN Ngadipuro 04 students in Blitar Regency, totaling 20 students. Data collection with observation, interview, questionnaire, and test techniques. The results of the Validity Test of Media Experts show an average of 98%, material experts 92%, and product feasibility results show an average of 94%included in the very valid category. The results of self efficacy and the problem of the problem were carried out using the n gain test with a problem solving results of 0.5974 which showed a moderate category, and self efficacy 0.8827 which showed a high category. Based on research result, the Media Diosia based on QR Code Sanagt Valid, and is effective for increasing self efficacy and problem solving in grade V SDN Ngadipuro 04 students.